(untitled) (Journal of the College of Basic Education, 2020)
This thesis study The system and its effect in determining the characteristic of the shape in contemporary Iraqi ceramics(Iraqi potters are a model),We have four chapters in this study, the first chapter consist of research problem, the importance of research, objectives, and limits, has been identified within three limits, objectivity, which included the impact of the system in determining the characteristic form, and the time between (2011 – 2019), and the Spatial in Iraq, and in Chapter II, it included the theoretical framework that Structure in one chapter which is installation systems in the ceramic form. The third chapter is represented by the research analysis and monitoring procedures of the research community, which consists of a group of ceramics for a group of ceramics for the period, and the sample was produced intentionally according to a number of factors highlighted by personal and artistic biography and the researcher chosen 8 sample and Analyze them within the criteria and indicators of the theoretical framework of the method of descriptive method of surveying and analyzing those ceramic works through the method of description, research, extrapolation and reliance on studies and scientific research that dealt with the content analysis of ceramic works in Iraq. The fourth chapter was concerned with the findings, conclusions and recommendations.